The longer, the better? Assessing the results of an eight-year citizen science initiative targeting protected insect species - Gisondi, Silvia; Lenzi, Alice; Bardiani, Marco; Blandino, Cristina; Hardersen, Sönke; Maurizi, Emanuela; Mosconi, Fabio; Nardi, Gianluca; Roversi, Pio Federico; Campanaro, Alessandro (Frontiers in Environmental Science, 2025)
BackgroundCitizen science has been proven to be a valuable approach to collect data at large scales and can be of particular interest especially if it meets the requirements of the Habitats Directive, a key piece of European Union environmental legislation that orients policies of member states about conservation actions and protected species and habitats monitoring. In Italy, only few citizen science projects are dedicated to the collection of data on insect species, and rarer are those focusing on protected insect species. A long-term initiative focused on protected species and habitats started in 2012 as the “LIFE MIPP” project and continued afterwards as the “InNat” project up until 2024. The above-mentioned initiative focused on 40 protected targets, including insects, crustaceans, plants and habitats.ResultsA total of 6,130 records, collected by more than 1,400 volunteers between 2014 and 2021, were analyzed focusing on the increase of the distributional knowledge of nine insect species. On average, 83% of records were considered valid in terms of correct species identification, with more than 60% of records collected outside protected areas. Analyses revealed a clear statistically significant increase in the number of records and in distributional data coverage over the years (i.e., number of occupied UTM cells and variation of shape/density of data distribution), though most of the considered species did not reach ‘saturation’ yet.ConclusionOur project significantly contributed to increase knowledge on the distribution of protected insect species thus stressing the importance of similar long-term initiatives, also fostering a more conscious management and design of protected areas.